Electronic Commerce information technology infrastructure : in-depth case studies to identify the framework, parameters and characteristics of Electronic Commerce information technology infrastructure. - Lee, Shane Tai Hsiung. (2008)
The focus of the study is to identify the e-commerce technology infrastructure models used by businesses and clarify their features, implementation and operations in relation to their e-commerce activities.